Optimizing the Representation of Facial Muscle Anatomy in 3D Animation Expressions - Pirmansah, Imam Ainudin; Rahman, Ahmad Zaid; Satria, Dhimas Adi (SINTA Journal (Science, Technology, and Agricultural), 2024)
This research aims to optimize the representation of facial muscle anatomy in 3D animated expressions by using a hybrid approach that combines blendshape and joint-based rigging techniques as well as an advanced control system. Blendshape is used to capture fine details and nuances of facial expressions, while joint-based rigging provides additional flexibility for broader, more dynamic movements. The implemented control system allows precise and interactive manipulation of various facial expressions, resulting in more realistic and natural facial deformations.Â The research methodology includes the development of a facial model with accurate anatomical details, followed by the implementation of a hybrid rig that combines blendshape and joint-based rigging. The control system is built using a node connector technique, which allows granular regulation of facial expression and deformation parameters. Validation was carried out through extensive testing with various facial expressions to assess the accuracy and realism of the resulting animation.Â The research results show that this hybrid approach significantly increases the accuracy and realism of facial expressions in 3D animation compared to conventional methods. The control system developed also proved effective in providing flexibility and ease of use for animators. Thus, this research offers an important contribution to improving the quality and efficiency of 3D animation production, as well as opening up opportunities for further development in facial rigging and animation techniques.